Increasing the level of automation of dispatch control when regulating at the end stops of public transport routes - Voronov, P O; Kudryavtsev, A A; Filippova, N A (IOP conference series. Materials Science and Engineering, 2021)
The subject of research is automated dispatch control of public transport. Smart systems application on transport started in the second half of the 20 th century. Application of such systems aims to improve every aspect of public transportation. However, despite constant development of telematics systems in public transport, this has not been achieved yet. The article discusses the use of telematics in public transport and the existing and actually functioning systems: ASK, NimBus and Navitrans. Authors suggest algorithm for public transport control that should increase the level of automation of dispatch control. The result of such approach is the improved regularity of public transport which is one of the key points to public transport efficiency and comfort to passengers.